(3HZjI GdhYGg aj WHbGJ GddZhjjf hGdfMGIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg NGdb GdhLhO GeG HYO aEfi efP fTCJ hCfG GJThb Edi cJGH jLeY GNHGQ GdfMhjjf s
(3BNQgG (B:s
(3bGd GHf GdRHjQ hcGf YGQakG HGdfMh hGdCOH Ohi Yf CHj GdbGSe s
(3GfXQ GdbSe GdChd ef GdJGQjN Qbe (B92s
(3QJHg Ydi MQha GdYLes
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B156 ; (3HQhcdeGf edMb (B- - (3U (B195 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B48 s
Keywords: (3GdJGQjNs